1991
DOI: 10.1002/mrd.1080300415
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a soluble acrosome reaction‐inducing factor, different from serum albumin, associated with the ovulated egg‐cumulus complex

Abstract: Soluble extracts of the ovulated hamster egg-cumulus complex (ECC) were tested on capacitated sperm for activity in inducing the physiological acrosome reaction (AR). Evidence for occurrence of the physiological AR included enhanced sperm penetration of intact homologous zonae pellucidae as well as induction of AR in nonattached and in zona-bound sperm following a brief coincubation with test compound. Since hamster serum albumin, a major protein of hamster body fluids, also induces spontaneous ARs under certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…The importance of cumulusexpansion was also supported by the low fertilizability of cumulus-free oocytes in the present study and previous reports [17,18]. Boatman and Robbins [19] reported that a soluble factor, possibly bound to the surface of the cumulus cells, promoted the acrosome reaction and increased fertilization rate. Therefore, cumulus cells might secrete some factors promoting fertilization into the expanded cumulus matrix.…”
Section: Fig 1 the Fertilization Rates Of Oocytes Matured In Vivosupporting
confidence: 90%
“…The importance of cumulusexpansion was also supported by the low fertilizability of cumulus-free oocytes in the present study and previous reports [17,18]. Boatman and Robbins [19] reported that a soluble factor, possibly bound to the surface of the cumulus cells, promoted the acrosome reaction and increased fertilization rate. Therefore, cumulus cells might secrete some factors promoting fertilization into the expanded cumulus matrix.…”
Section: Fig 1 the Fertilization Rates Of Oocytes Matured In Vivosupporting
confidence: 90%
“…For egg penetration experiments, cauda epididymal sperm were obtained undiluted under oil and, afier staggering inseminations by 2-5 min, incubated under capacitating conditions (2-4 X 106/ml) for 5 h in medium TAW-WA with sperm motility factors as previously described [16,17,39,40]. Then sperm were diluted 1:10 into drops of TALP-PVA containing 14-16 follicular eggs + biological factors.…”
Section: Sperm Preparation and Egg Penetration Bioassaymentioning
confidence: 99%
“…Cumulus oophorus fluid (COF) eluate was prepared as previously described [16,17]. OVN was isolated from excised oviducts of mature female hamsters (n = 6 hamsters per collection) that were injected with 25 IU of eCG (Diosynth, Chicago, IL) on the morning of the post-estrus discharge [34] and then killed by cervical dislocation at 1500 h on Day 4.…”
Section: Preparation Of Biological Test Fluidsmentioning
confidence: 99%
See 2 more Smart Citations